CircBAZ1B stimulates myocardial ischemia/reperfusion injury (MI/RI) by modulating miR-1252-5p/ATF3-mediated ferroptosis - Ruili Wei; Tianxiao Yang; Weihong Li; Xiqian Wang (Archives of Medical Science)
Introduction Circular RNAs (circRNAs) have been implicated in myocardial ischemia (MI)/reperfusion injury (RI), yet their essential roles in MI/RI-induced ferroptosis have not been fully elucidated. Here, we focused on the biological function and regulatory mechanism of circBAZ1B, a circRNA derived from the bromodomain adjacent to the zinc finger domain 1B (BAZ1B) gene, in MI/RI progression.